Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Let f be the function defined by

f= {(-3,4),(-2,2),(-1,0),(0,1),(1,3),(2,4),(3,-1)}

and let g bed the function defined by

g={(-3,-2),(-2,0),(-1,-4),(0,0),(1,-3),(2,1),(3,2)}

Compute the indicated value if it exists

a. Compute: (f+g)(-3). What does this answer mean in relation to the two functions?

b.Compute: (f-g)(2). Why does it matter which order we subtract the functions? What changes occur if we subtract f from g or (g-f)(2)?

c. Compute: (fg)(-`1). Explain your reasoning in this answer.

d. Compute: (gf)(-3). Does it matter which order we multiply in ?


Sagot :

Answer:

  • See below

Step-by-step explanation:

a) Sum of two functions

  • f(-3) = 4, g(-3) = - 2 (from given sets of data)
  • (f + g)(-3) = f(-3) + g(-3) = 4 + (-2) = 2

b) Difference of two functions

  • f(2) = 4, g(2) = 1 (from given sets of data)
  • (f - g)(2) = f(2) - g(2) = 4 - 1 = 3

c) Product of two functions

  • f(-1) = 0, g(-1) = - 4 (from given sets of data)
  • (fg)(- 1) = f(-1)*g(-1) = 0*(-4) = 0

d) Product of functions, fg = gf, same result with different order

  • g(-3) = -2, f(-3) = 4 (from given sets of data)
  • (gf)(- 3) = (-2)*4 = - 8

Answer:

(a) (f + g)(-3) = 2

(b) (f - g)(2) = 3

(c) (fg)(-1) = 0

(d) (gf)(-3) = -8

Step-by-step explanation:

Function operations

(f + g)(x) = f(x) + g(x)

(f - g)(x) = f(x) - g(x)

(f · g)(x) = f(x) · g(x)

Question (a)

From the given data sets:

  • f(-3) = 4
  • g(-3) = -2

⇒ (f + g)(-3) = f(-3) + g(-3) = 4 + -2 = 4 - 2 = 2

Question (b)

From the given data sets:

  • f(2) = 4
  • g(2) = 1

⇒ (f - g)(2) = f(2) - g(2) = 4 - 1 = 3

(g - f)(2) = g(2) - f(2) = 1 - 4 = -3

The change that occurs between (f - g)(2) and (g - f)(2) is that one is the negative of the other.

Question (c)

From the given data sets:

  • f(-1) = 0
  • g(-1) = -4

⇒ (fg)(-1) = f(-1) · g(-1) = 0 · -4 = 0

Question (d)

From the given data sets:

  • f(-3) = 4
  • g(-3) = -2

⇒ (gf)(-3) = g(-3) · f(-3) = -2 · 4 = -8

If we change the order in which we multiply the functions, the answer doesn't change:

(fg)(-3) = f(-3) · g(-3) = 4 · -2 = -8

So it doesn't matter in which order we multiply.

Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.